Nucleoskeleton proteins for nuclear dynamics. (22nd January 2021) - Miyamoto, Kei; Harata, Masahiko
Abstract: The eukaryotic nucleus shows organized structures of chromosomes, transcriptional components and their associated proteins. It has been believed that such a dense nuclear environment prevents the formation of a cytoskeleton-like network of protein filaments. However, accumulating evidence suggests that the cell nucleus also possesses structural filamentous components to support nuclear organization and compartments, which are referred to as nucleoskeleton proteins. Nucleoskeleton proteins including lamins and actin influence nuclear dynamics including transcriptional regulation, chromatin organization and DNA damage responses. Furthermore, these nucleoskeleton proteins play a pivotal role in cellular differentiation and animal development. In this commentary, we discuss how nucleoskeleton-based regulatory mechanisms orchestrate nuclear dynamics.